PENGARUH PENDEKATAN KONTEKSTUAL BERBANTUAN MEDIA â€œBOCAH UNIKâ€ TERHADAP KEMAMPUAN PEMAHAMAN DAN KONEKSI MATEMATIS SISWA - Nurfalah, Evi; Irawati, Riana; Isrok'atun, I. (Jurnal Pena Ilmiah, 2017)
The research purposed are to knew influence by contextual approach with â€œBocah Unikâ€ to the mathematical understanding and studentâ€™s mathematical connections and how correlation from that ability. The method used is quasi experimental with the nonequivalent control group design. The sample are students of fourth grade elementary school from SDN Bendungan 2 as an experimental class and SDN Sukamulya as an controlling class. The instruments used are mathematical understanding test, Â mathematical connections test, observation sheet of teacher performance, observation sheet of student activities, student journals and field notes. The research results that mathematical understanding ability of conventional approach is better than contextual approach. While, mathematical connections ability of contextual approach is better than the control one. There is a correlation between mathematical understanding and mathematical connections ability. So, the student who has a good ability of mathematical understanding is inclined that the student has a good ability of mathematical connection.